Relationship between Innovation & Technology and Internationalization: Cluster Analysis in Europe and Central Asia - José, Pereira (2021)
Comunicação na Regional Helix '21 International Conference on Territorial Dimensions of Green and Digital Transitions - Lamego, Portugal 28-30 October 2021